Recuperação da informação no portal LTi - Barros, Niedja Nascimento (2023)
This project addresses the information actions in the information regime of the Laboratory of Intellectual Technologies Project - LTi from the perspective of information retrieval. Our purpose is to contribute to academic training in undergraduate and graduate courses at the Federal University of Paraíba. It is in this social and cultural space that the subjects who share a way of life act ― the academic way of life within the Information Science community ― and where domains, strata and modalities of information actions are intertwined, from their formative and relational, coordination, innovation, creation and ap-plication of theoretical models, emphasizing its mediation characteristic through the availability of vir-tual information artifacts and services. LTi's main product is the LTi Virtual Portal. Created concurrently with the project, the LTi Portal had its architecture and graphic design modified in 2019. In this process, the retrieval of information from the original Portal files (Memory) was not fully transferred to the Current Portal, so that the user can come having difficulty finding information that is available on the Memory Portal. It is necessary to retrieve the contents of the LTi Memória Portal, verifying if they are available in the new Portal, and create search and information retrieval consultation mechanisms, based on information actions, facilitating access to the contents for users. Therefore, the present project pro-poses to rescue the original functionality of the organization of the files and, also, to organize them, according to the information actions, as semantic trails for retrieving the information available in the files of the LTi Portal. This research intends to present a proposal for a authorized terms for Portal LTi, approaching Portal LTi from the perspective of organizing its content, with a view to better retrieving the information contained in the files made available on its pages.